16‐3: Study on Enhancement of the Sound Quality by Improvement of Panel Vibration in OLED TV. Issue 1 (30th May 2018) - Lee, Sungtae; Park, Kwanho; Jang, Kyeongkun; Oh, Changho
Abstract : With the remarkable development of TV technology, CRT has been evolving into LCD and OLED, and design is also developing as a Slim & Simple trend. In recent years, TVs have been designed so that the sound is reflected and heard by hiding the speaker behind the panel to differentiate the design. As a result, the sound quality is affected by the room environment (furniture arrangement, floor material, etc.) The number of viewers who purchase and install separate speakers is increasing. In this study, we investigated how to reduce the reflection sound by Standing wave by optimizing the enclosure shape in the CSO (Crystal Sound OLED) technology, which was the OLED panel developed last year by LG Display and used as speaker diaphragm. We want to improve peak and dip in frequency characteristics by improving abnormal vibration generated by panel speaker.